Compressive failure of hybrid multidirectional fibre-reinforced composites. (April 2015) - Tsampas, S.A.; Greenhalgh, E.S.; Ankersen, J.; Curtis, P.T.
Abstract: In this paper, the hybridisation of multidirectional carbon fibre-reinforced composites as a means of improving the compressive performance is studied. The aim is to thoroughly investigate how hybridisation influences the laminate behaviour under different compression conditions and thus provide an explanation of the "hybrid effect". The chosen approach was to compare the compressive performance of two monolithic carbon fibre/epoxy systems, CYTEC HTS/MTM44-1 and IMS/MTM44-1, with that of their respective hybrids. This was done by keeping the same layup throughout ((0/90/45/−45)2S ) while replacing the angle plies in one case or the orthogonal plies in the other case with the second material, thus producing two hybrid systems. To investigate the compressive performance of these configurations, compact and plain compression test methods were employed which also allowed studying the sensitivity of compressive failure to specimen geometry and loading conditions. The experimental results and the subsequent fractographic analysis revealed that the hybridisation of selective ply interfaces influenced the location and severity of the failure mechanisms. Finally, in light of this knowledge, an update of the generic sequence of events, previously suggested by the authors, which lead to global fracture in multidirectional fibre-reinforced composites under compression is presented.